Retrofit de estruturas: ênfase às soluções estruturais com aço - Filla, Nathaly Tauany (2017)
The difference between the Retrofit process and the traditional reform consists in the modernization of the building systems and preservation of the architecture. The concept of retrofit is to mix old and contemporary architecture to value the surroundings and history of the property. With popularization of this process, there are lots of examples that prove its efficiency and economic advantage when preliminary studies are made. The utilization of steel in this process is very promising since steel it is a material that has high strength, reliability and various other qualities which can be to be considered suitable in this process. The present work has as purpose to explore and analize the Retrofit, exposing and discussing the advantages of the use of steel in the process, presenting real and successful examples in various situations.